Dynamics of Covid-19 policy implementation in DKI Jakarta: study of the responses of Muhammadiyah members - Fajar Riza Ul Haq; Hadna, Agus Heruanto; Darwin, Muhadjir; Ikhwan, Hakimul (Indonesian Journal of Islam and Muslim Societies, 2024)
Abstract This study aims to map the dynamics of Muhammadiyah DKI Jakarta members’ responses to the handling Covid-19 policies and seek explanations of variations in responses from the perspective of political partisanship as a determining factor in the process of evaluating citizens against government policies. Qualitative method is used revealing factors influencing the emergence of different responses to three pandemic management policies: mobility restrictions, 3M campaigns (wearing masks, washing hands, keeping distance), and vaccinations. There are two findings of this research. First, the implementation of the Covid-19 policy has given rise to two clusters of responses among Muhammadiyah DKI Jakarta members, namely Affirmation (fully accepting) and Hesitancy, an attitude of doubt that gives rise to negotiation (selective acceptance), and resistance (complete rejection). Second, these variations in response represent the process of contestation of several factors in responding to pandemic policy against the background of political polarization of the leadership of the Governor of DKI (Anies Baswedan) and the Central Government (President Jokowi), namely political trust and distrust, knowledge construction, and political partisanship. Two study recommendations: first, the need for political partisanship and policy synchronization between the central and provincial governments in responding to non-natural disaster issues which demand alertness and innovation from policy makers. Second, the need for the government’s cultural sensitivity appointing the implementation of its policies to not widen polarization and provoke sentiments of political partisanship in society.